Comparative efficacy of femoral neck system vs. cannulated compression screws in young patients with femoral neck fractures: a systematic review and meta-analysis - Zhang, Weishuai; Yang, Nannan; Zhu, Xianyou; Lu, Xuchao; Cheng, Jian (Frontiers in Surgery, 2025)
BackgroundThe optimal method for internal fixation of femoral neck fractures in younger individuals remains a subject of debate. This meta-analysis systematically evaluates and compares the clinical outcomes of the femoral neck system (FNS) and cannulated compression screws (CCSs) within this demographic.MethodsA comprehensive literature search was conducted across the Cochrane Library, PubMed, Web of Science, and Embase databases, covering studies from their inception through March 2024. The search targeted cohort studies that compared FNS (n = 265) and CCSs (n = 326) in patients aged 14–65 years with femoral neck fractures. The methodological quality of the studies was appraised using the Newcastle–Ottawa Scale. Statistical analyses were executed using RevMan 5.4, with results presented as standardized mean differences (SMDs) or weighted mean differences (WMDs), accompanied by 95% confidence intervals (CIs).ResultsThe analysis incorporated nine high-quality cohort studies involving 591 patients who underwent surgical procedures for femoral neck fractures. Of these patients, 265 were treated with the femoral neck system (FNS), while 326 were treated with CCSs. Meta-analysis revealed that, compared to CCS, FNS was associated with a significantly shorted fracture healing time (SMD = 16.30, 95% CI: 3.79–28.82, P < 0.001), decreased intraoperative fluoroscopy usage (WMD) = −8.14, 95% CI: −9.82 to −6.46, P < 0.001), and higher Harris hip scores at the final follow-up (WMD = −3.43, 95% CI: −4.08 to −2.77, P < 0.001). In addition, the FNS group exhibited a lower incidence of postoperative complications, including urinary tract infections, venous thromboembolism, non-union, screw loosening, and femoral head necrosis [risk ratio (RR) = 1.05, 95% CI: 0.92–1.19, P = 0.50]. However, the FNS was associated with a longer surgical incision (WMD = 0.84, 95% CI: 0.55–1.13, P < 0.001) and increased intraoperative blood loss (WMD = 16.30, 95% CI: 3.79–28.82, P = 0.01). The analysis revealed no statistically significant differences between the two techniques in terms of operation duration (WMD = −4.88, 95% CI: −12.25 to 2.48, P = 0.19), length of hospital stay (WMD = 0.10, 95% CI: −0.20 to 0.40, P = 0.52), or the excellent-to-good rate at the final follow-up (RR = 1.05, 95% CI: 0.92–1.19, P = 0.50).ConclusionsThe femoral neck system (FNS) may present potential benefits in specific outcomes, notably expedited healing and enhanced functional rehabilitation. The results of this study advocate for the consideration of the FNS as a preferred treatment option for active patients, where minimizing radiation exposure and optimizing long-term outcomes are prioritized, despite its slightly greater invasiveness.